Modification of Silica Rice Husk Ash to Solid Ammonium Sulphate for Second Generation Biofuels Productions. (9th December 2014) - Hello, Kasim Mohammed; Mohammed, Majid Jari; Yasser, Asstabraq Mohsen; Adam, Farook; Farag, Zinab
Abstract : A new approach has been demonstrated for the synthesis of solid ammonium sulphate attached to silica rice husk ash. The 3-(aminopropyl)triethoxysilane was immobilized onto silica at room temperature to functionalize the silica with ammine end groups (–NH2 ). The amine group was sulphated with sulphuric acid to produce a novel micro-rod-like shaped acidic catalyst (as seen with TEM) designated RHNH3 SO4 H (RH = rice husk). The TGA analysis shows that the catalyst is stable at temperatures below 200°C. The acidity measurement of the catalyst indicates that it has Brønsted acid sites. Cellulose extracted from waste of rice husk and cellulose extracted from office paper were hydrolysed to glucose in 6 h, and the glucose was hydrolysed afterwards to other products within 13 h. The catalyst is reusable many times without a significant loss of catalytic activity.